INDONESIAN HIGH SCHOOL STUDENT’S ABILITY IN COMPREHENDING NARRATIVE TEXTS - Damayanti, Eka; Supriusman; Azhar, Fadly (Prodi Administrasi Pendidikan Program Pascasarjana Universitas Riau, 2024)
This study aims to investigate students’ ability to comprehend narrative text. This study was conducted at one school in Riau Island province. The name of the school is deliberately anonymous considering the research ethics. Eighty students were recruited and participated in this study while 28 of them were selected as the sample using purposive sampling. To attain data, five sets of narrative text questions were employed. Each set comprises eight questions that indicate reading components; factual information, main ideas, meaning of certain words, references, generic structure, language features, and social functions. Data were calculated by using Microsoft Excel 2016. The findings show that the mean score of their ability in comprehending components of reading was 47% while comprehending narrative texts at 53% so their total at 50% and categorized into medium level. The finding of research also showed that the lowest ability for students was in answering questions about finding the meaning of certain words at 43%. It is suggested that students must do more practice in reading, then they should learn more about the eight components of reading comprehension of narrative texts such as factual information, main ideas, vocabulary, references, inferences, generic structure, language features, and social functions. Then learn reading strategies such as schema, skimming and scanning.